Réponses

  • Utilisateur Brainly
2014-04-12T17:38:18+02:00
Calculer les expressions suivantes :

3 X (2/4) + 5 X (4/3)
= (3 X 2)/4 + (5 X 4)/3
= 6/4 + 20/3
= (6 X 3)/(4 X 3) + (20 X 4)/(3 X 4)
= 18/12 + 80/12
= 98/12
= 49/6

1 + 10 + 10/2 + 10/3 + 10/4 + 10/5
= 11 + 5 + 10/3 + 10/4 + 2
= 18 + (10 X 4)/(3 X 4) + (10 X 3)/(4 X 3)
= 18 + 40/12 + 30/12
= 18 + 70/12 
= (18 X 12)/12 + 70/12
= 216/12 + 70/12
= 286/12
= 143/6

1 - 3/2 X (-5)/2
= 1 - (-5 X 3)/(2 X 2)
= 1 - (-15)/4
= 1 + 15/4
= 4/4 + 15/4
= 19/4

2/3 X -9 + 3/3 - (5/2 + 2 - 1)
= 2/3 X -9 + 1 - 5/2 - 2 + 1
= (2 X (-9))/3 - 5/2
= (-18/3) - 5/2
= (-18 X 2)/(3 X2) - (5 X 3)/(2 X 3)
= - 36/6 - 15/6
= -51/6
= -17/2
2014-04-12T18:01:45+02:00
Calculer les expressions suivantes :

3 x (2/4) + 5 x (4/3)
= 3 x 2 + 5 x 4
      4        3
= 6/4 + 20/3
= 6 x 3 / 4 x 3 + 20 x 4 / 3 x 4
= 18/12 + 80/12
= 98/12
= 2 x 49 / 2 x 6
= 49/6

1 + 10 + 10/2 + 10/3 + 10/4 + 10/5
11 + 10/2 + 10/3 + 10/4 + 10/5
11 x 60 / 1 x 60 + 10 x 30 / 2 x 30 + 10 x 20 / 1 x 20 + 10 x 15 / 4 x 15 + 10 x 12 / 5 x 12
= 660/60 + 300/60 + 200/60 + 150/60 + 120/60
= 1430/60
= 10 x 143 / 10 x 6
= 143/6


1 - 3/2 x (-5) / 2
= 1 - 3 x -5
        2 x 2
= 1 + 15/4
= 1 x 4 / 1 x 4 + 15/4
= 4/4 + 15/4
= 19/4

2/3 x -9 + 3/3 - (5/2 + 2 - 1)
= 2 x -9 + 3/3 - (5/2 + 2 x 2 / 1 x 2 - 1 x 2 / 2 x 2)
   3 x 1
= -18/3 + 3/3 - (5/2 + 4/2 - 2/2)
= -18/3 + 3/3 - 7/2
= - 18 x  2 / 3 x 2 + 3 x 2 / 3 x 2 - 7 x 3 / 2 x 3
= -36/6 + 6/6 - 21/6
= -51/6
= 3 x -17 / 3 x 2
= -17/2